Dynamic assessment of innovative retrofit techniques for masonry buildings. (15th August 2018) - Maddaloni, Gennaro; Di Ludovico, M.; Balsamo, A.; Maddaloni, Giuseppe; Prota, A.
Abstract: Recent earthquakes gave further awareness on seismic risk and vulnerability of existing buildings, especially for the protection of historical-artistic value of old town centers. The preservation of the architectonical value of historical buildings needs to be combined with the structural safety; this goal can be pursued by means of proper structural analyses and strengthening interventions by means of innovative techniques. A study on the dynamic response of a scaled one-story building, made by yellow regular Neapolitan blocks and mortar with poor mechanical properties in a traditional texture of existing masonry structures, is herein illustrated. The seismic response of the masonry building has been investigated by means of shake-table tests on 1/2-scale model. Seismic inputs of last devastating earthquakes happened in Italy (e.g. L'Aquila 2009, Amatrice 2016) were used in order to investigate the seismic behavior of the sample. Then the effectiveness of a repair/strengthening strategy based on the use of innovative techniques was experimentally investigated. The repair was made by the combined use of injection of cracks with cement-free, lime-pozzolan based mortar and innovative helical stainless steel bars with dry application. The strengthening consisted of a Fiber Reinforced Cementitious Mortar (FRCM) wrapping at the lintel level to avoid out of plane mechanisms and of a fiber reinforced plaster of walls for in plane strengthening. The repair/strengthening intervention promoted a global structural behavior and led to a significant increase of the specimen seismic performance.